Personality Profile - Dhungel, Dwarika Nath (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
In light of recent developments in water resources and hydropower development in Nepal, HYDRO Nepal felt this an appropriate moment to review some of the personalities who have played important roles in these areas over the past few decades. HYDRO Nepal considers it appropriate to underline the profile Dr. Dwarika Nath Dhungel to its readers. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 20 Page: 68-73